Penerapan Manajemen Pendidikan Untuk Meningkatkan Prestasi Keagamaan Santri - Ita Nurmalasari (CV. ULIL ALBAB CORP, 2024)
Aplication of management of edication to improve performance of religion in An-Nawawi Pondok Pesantren An-Nawawi Purworejo. The purpose of this research is to analyze how to apply management of education to improve performance of religion of An-Nawawi Pondok Pesantren An-Nawawi. And also to know supparting and inhibiting factors on it, This research use field research as the type of research, it is that used in a row with learning, analyzing, loaking in to field material that has relehance with the object of research. This result of this research shows that thw aplication of mangement in An-Nawawi Pondok Pesantren An-Nawawi, Purworejo is relevant with the function of islamic management of education, it is planning, organizing, moving, oversighting. On improve performance An-Nawawi Pondok Pesantren An-Nawawi declare a additional study.